Different profiles of circulating arginase 2 in subtypes of preeclampsia pregnant women - Bertozzi-Matheus, Mariana [UNESP]; Bueno-Pereira, Thaina Omia [UNESP]; Viana-Mattioli, Sarah [UNESP]; Carlstrom, Mattias; Cavalli, Ricardo de Carvalho; Sandrim, Valeria Cristina [UNESP] (Elsevier B.V., 2021)
Background and aims: Preeclampsia (PE) is a gestational hypertensive disease responsible for high maternal and fetal morbidity and mortality. The increase in blood pressure is associated with a decrease in the bioavailability of nitric oxide (NO). Arginase interferes with NO production consuming L-arginine, a substrate required by endothelial NO synthase to NO formation. No previous study has quantified the circulating levels of the two arginase isoforms (arginase 1 and arginase 2) in the plasma of pregnant women with PE. Therefore, our objective is to evaluate these plasma levels in healthy pregnant women and PE with or without severe features and who respond or not to antihypertensive therapy. Methods: We compared 29 healthy pregnant women with 56 pregnant women with PE, who were also divided into with severe features (n = 24) or without severe features (n = 32) and into responsive (n = 29) or nonresponsive to antihypertensive therapy (n = 27). We quantified the plasmatic expression of arginase 1 and arginase 2 by ELISA kits. Results: While similar levels of arginase 1 were found among groups, lower arginase 2 plasma levels were found in PE without severe features and responsive to antihypertensive drugs when compared to healthy pregnant women. There was no difference between arginase 2 levels in PE with severe features and nonresponsive group when compared to healthy pregnant women. Conclusion: This shows different circulation profiles of arginase 2 among groups, suggesting the existence of mechanisms of arginase 2 modulation in pregnant women with PE associated with the severity of the disease and responsiveness to antihypertensive treatment.
Keywords: Preeclampsia; Arginase; Nitric oxide; Blood pressure; Pregnancy; antihypertensive drugs